2009
DOI: 10.1038/nature08235
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of induced pluripotent stem cell generation by the p53–p21 pathway

Abstract: Induced pluripotent stem (iPS) cells can be generated from somatic cells by introduction of Oct3/4, Sox2, Klf4 and c-Myc, in mouse 1-4 and human [5][6][7][8] . Efficiency of this process, however, is low 9 . Pluripotency can be induced without c-Myc, but with even lower efficiency 10,11 . A p53 siRNA was recently shown to promote human iPS cell generation 12 , but specificity and mechanisms remain to be determined. Here we report that up to 10% of transduced mouse embryonic fibroblasts (MEF) lacking p53 became… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,051
4
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,221 publications
(1,123 citation statements)
references
References 23 publications
61
1,051
4
7
Order By: Relevance
“…Only a few cells can overcome this barrier and become iPSCs. A number of studies demonstrated that when key components (such as p53 and p21) of the DNA damage pathway were deleted, the percentage of iPS cell generation significantly increased (Zhao et al, 2008a;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b). Suppression of the p53 pathway may compromise a cell's genome stability.…”
Section: Overcoming the Dna Damage Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Only a few cells can overcome this barrier and become iPSCs. A number of studies demonstrated that when key components (such as p53 and p21) of the DNA damage pathway were deleted, the percentage of iPS cell generation significantly increased (Zhao et al, 2008a;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b). Suppression of the p53 pathway may compromise a cell's genome stability.…”
Section: Overcoming the Dna Damage Responsementioning
confidence: 99%
“…As the DNA damage pathway poses a major barrier towards regaining pluripotency (Zhao et al, 2008b;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b), chemical compounds that alleviate the stress of DNA damage response may help cells to overcome this barrier. To this end, Vitamin C has been shown to significantly increase the formation of both mouse and human iPSC by suppressing p53 induced cell senescence (Esteban et al, 2010).…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…17 Numerous studies using viral vectors or cDNA plasmids to generate transgene-expressing clones have observed repression of transgene expression. [18][19][20][21][22] In this study, X92% FVIII-PACs randomly integrated into the hiMSC host genome, whereas independently segregating FVIII-HACs persisted in X90% of the cells as determined by FISH analysis. Therefore, our results suggested that reductions in transgene expression in the FVIII-PAC transfected hiMSC cells were caused by silencing rather than by loss of the transgene itself.…”
Section: Discussionmentioning
confidence: 58%
“…Established GSCs from p53 knockout mice generate ES-like cells at a higher rate compared to wild-type, even after long periods in culture, indicating that p53 negatively controls the reprogramming process (Kanatsu-Shinohara et al, 2004). The importance of p53 activity has been confirmed in a series of publications describing enhanced iPS formation by p53 knockout or knockdown, although SSC reprogramming may not always take the same route before pluripotency is achieved (Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009). Genetic and epigenetic alterations of other tumor suppressors and cell cycle regulators are known to affect cell reprogramming and ES cell maintenance (Boominathan, 2009;Ruiz et al, 2011).…”
Section: Factors Affecting Reprogramming Efficiencymentioning
confidence: 96%